Extraction Of Secondary Metabolite In Tetraselmis Suecica Using Different Solvent Polarity - Alif Faiz Mohd Din, Muhammad (Pusat Pengajian Teknologi Industri, 2020)
Recently, there has been much interest in secondary metabolites extracted from natural sources including microalgae for the food industry as well as pharmaceutical, cosmetic, and nutraceutical sectors. These interests have been increasing among researchers nowadays. Therefore, the present investigation was undertaken to analyse the secondary metabolite from Tetraselmis suecica which is a marine microalga. Briefly, T. suecica was cultured in normal conditions in the F/2 medium. During 15 days of monitoring of the cell growth, the absorbance reading at 680 nm was recorded. Then, its biomass was further extract by using solvent extraction method. Further, the extract was obtained using different solvent polarity which are hexane, ethyl acetate, and methanol. The yield extract was calculated and was revealed that extraction using hexane as solvent was the best among those three solvents. The resulted extract using different solvent polarities was further analyse using GC-FID. There were several peaks present in the chromatogram of extract using the solvents tested, however, there is no peak in the chromatogram of extract using methanol. This can be concluded that there was a compound which is C10 (Methyl Decanoate) in the chromatogram of extract using hexane and several compounds in the chromatogram of extract using ethyl acetate such as C10 (Methyl Decanoate), C12 (Methyl Dodecanoate) and C14 (Methyl-Cis-9- Tetradecanoate)